2007
DOI: 10.1002/gps.1827
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity of depressed elderly inpatients

Abstract: Depressed elderly Australian inpatients are less religious than their North American counterparts. Nevertheless, religion remains important for a large minority of such individuals. Clinicians need to be aware that such individuals may turn to religion when depressed, especially to cope with the presence of physical disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
2
18
1
2
Order By: Relevance
“…Our review uncovered many studies examining connections between R/S, depression, and anxiety. Of 444 studies assessing relationships between R/S and depression, 272 (61%) reported lower depression among the more R/S, including 119 (67%) of the 178 highest quality studies [82][83][84]. Of 299 studies examining relationships with anxiety, 147 (49%) reported inverse associations with R/S, and of the 67 highest quality studies, 38 (55%) did so [85][86][87].…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Our review uncovered many studies examining connections between R/S, depression, and anxiety. Of 444 studies assessing relationships between R/S and depression, 272 (61%) reported lower depression among the more R/S, including 119 (67%) of the 178 highest quality studies [82][83][84]. Of 299 studies examining relationships with anxiety, 147 (49%) reported inverse associations with R/S, and of the 67 highest quality studies, 38 (55%) did so [85][86][87].…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…It would be a grave mistake to treat all faith communities as homogenous (Leavey & King, 2007), and the few Australian studies published on religiosity and health have taken this into account by focusing on specific age groups (Law & Sbarra, 2009;Payman, George, & Ryburn, 2008) or various ethnic communities (Chan, 2009). However, there are still many gaps within our understanding of Australian mental health treatment outcomes and religiosity.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, using a sample of 122 Christian persons, Ryan and Francis (2012) used several variables from the Spiritual Assessment Inventory (Hall & Edwards, 2002) to quantify awareness of God in an effort to capture the presence of God in each participant's daily life, including impression management to measure spiritual behaviour and instability, which tries to capture the anxiety that stems from religious belief -such as being abandoned by God. Patient Religiosity was also measured in Payman et al (2008) study on depressed elderly Australians by the Duke University Religion Index (Koenig, George, & Peterson, 1997) -this five item scale asked about frequency of religious attendance, frequency of participation in private religious activities such as prayer, meditation, or Bible study, and intrinsic religiosity which asks patients to rate themselves to these questions: "My religious beliefs are what really lies behind my whole approach to life," "I try hard to carry my religion over into all other dealings in life," and, "In my life, I experience the presence of the Divine." Hilbers et al (2010) sample consisted of hospital patients.…”
Section: Mental Health Religion and Culturementioning
confidence: 99%
See 2 more Smart Citations